Positioning of psychodynamic psychotherapy in the treatment of depression: A comparison of the RANZCP 2020 and NICE 2022 guidelines. (June 2023) - Malhi, Gin S; Bell, Erica; Bassett, Darryl; Boyce, Philip; Hazell, Philip; Hopwood, Malcolm; Lyndon, Bill; Mulder, Roger; Porter, Richard; Murray, Greg
Objective: To compare the 2022 NICE guidelines (NG222) and 2020 RANZCP clinical practice guidelines (MDcpg 2020 ) recommendations for the treatment of depression using psychodynamic psychotherapy. Conclusions: Both guidelines recommend psychological interventions first-line. However, only short-term psychodynamic psychotherapy (STPP) is recommended, and in the NG222 it is ranked last for less severe depression and 7th for more severe depression. In contrast, cognitive behavioural therapy and behavioural activation are deemed the more clinically effective and cost-effective psychological therapies. And antidepressants play a significant role – largely in more severe depression.